Provider Attitudes and Practices Regarding Maternal Vaccination Among Obstetrician-Gynecologists: A National Survey. (4th October 2017) - O'Leary, Sean; Riley, Laura; Lindley, Megan C; Allison, Mandy; Crane, Lori; Hurley, Laura; Beaty, Brenda; Brtnikova, Michaela; Albert, Alison; Fisher, Alison; Jiles, Angela; Kempe, Allison
Abstract: Background: Obstetrician-gynecologists (ob-gyns) play a crucial role as vaccinators of pregnant women, yet little is known about their attitudes and practices in this role. Our objectives were to describe, among a nationally representative sample of ob-gyns: 1) practices and attitudes regarding vaccination of pregnant women; and 2) barriers to the use of standing orders. Methods: An e-mail and mail survey among ob-gyns conducted March-June 2016. Results: The response rate was 69% (331/477). Overall, 90% reported administering ≥1 vaccines to pregnant women. Almost all (97% and 95%, respectively), strongly recommend influenza (flu) and tetanus-diphtheria-acellular pertussis (Tdap) vaccines; 60% use standing orders for flu vaccination and 56% for Tdap vaccination. More (68%) always recommend Tdap vaccines to household contacts of pregnant women than flu vaccines (53%). Physician attitudes are shown in the figure. The most significant barriers to the use of standing orders included provider concern that patients prefer to speak to them first (12% major barrier, 25% somewhat), provider belief that they should be the one to recommend vaccines (11% major, 12% somewhat), and staff discomfort because of having to answer vaccine-related questions (7% major, 17% somewhat). Conclusion: Ob-gyn attitudinal barriers to maternal vaccination are rare, whereas barriers to use of standing orders, a highly effective strategy for increasing vaccination uptake, are common, and less than 2/3 of providers currently use them. Disclosures: All authors: No reported disclosures.